Uncertainty in Depth Evaluation of Partially Conductive Cracks from Eddy Current Testing Signals - Ladislav Janousek; Milan Smetana (Communications - Scientific letters of the University of Zilina, 2011)
The paper deals with eddy current non-destructive evaluation of partially conductive cracks. Especially, uncertainty of a depth estimation of such cracks from eddy current testing signals is considered here. A plate specimen having the electromagnetic parameters of a stainless steel SUS316L is inspected in this study by numerical means. A crack with variable depth, width and conductivity is positioned in the middle of the plate. One of the most utilized eddy current probes so called pancake probe is employed for the inspection. Response signals of the crack with different parameters are numerically calculated and further analysed. Presented results clearly demonstrate that the uncertainty of a crackdepth estimation considerably increases when conductive cracks are evaluated comparing to non-conductive cracks.